The Impact Of Brand Image and Promotion on Customer Loyalty - Haryadi, Imam; Syharuddin, Syharuddin (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2023)
Grab indeed is a big company that provide service of ride and food delivery. The question is whether the brand image of Grab with its product Grabfood gain customer loyalty or their promotion reach the customer loyalty or even both variables are influence customer loyalty. Some researches discussed that both variables are influences customer loyalty. On the other hand, there are researches that stated that brand image has no effect on customer loyalty as well as promotion has no impact on customer loyalty. It is important to investigate whether the brand image of Grab and its promotion able to influence the customer loyalty directly without customer satisfaction. Moreover, this study is conducted at Ponorogo regency which few of similar platform compete each other. This study aims to investigate the impact of brand image and promotion on customer loyalty. The method employed in this study is a qualitative method. Multiple regression analysis was used to analyzed the data through SPSS 20 aplication. The data was obtained using servey questionnaire. The population of this study is 12.422. Therefore, using Slovin technique the sample size of this 99 respondents. The result of this study indicates that promotion partially impacting customer loyalty while brand image partially has no effect on customer loyalty. Meanwhile, simultanousely promotion and brand image influence customer loyalty. The level of impact of promotion and brand image are about 53.3% while the rest of it about 46.7% are impacted by other factor excluded from this study. The result of this study is quite strong, therefore, it is important for Grab to take an account on their brand image, since Grab already have an enormous promotion in several platform of media social. Brand image probably could be erupted by the Grab partner (driver) therefore it is important to maintain the relationship with the partner.